Strategies for the identification of novel inhibitors of deubiquitinating enzymes. (19th September 2008) - Goldenberg, Seth J.; McDermott, Jeffrey L.; Butt, Tauseef R.; Mattern, Michael R.; Nicholson, Benjamin
Abstract : Dysregulation of the UPS (ubiquitin–proteasome system) has been implicated in a wide range of pathologies including cancer, neurodegeneration and viral infection. Inhibiting the proteasome has been shown to be an effective therapeutic strategy in humans; yet toxicity with this target remains high. DUBs (deubiquitinating enzymes) represent an alternative target in the UPS with low predicted toxicity. Currently, there are no DUB inhibitors that have been used clinically. To address this situation, Progenra has developed a novel assay to measure the proteolytic cleavage of Ub (ubiquitin) or UBL (Ub-like protein) conjugates such as SUMO (small Ub-related modifier), NEDD8 (neural-precursor-cell-expressed, developmentally down-regulated 8) or ISG15 (interferon-stimulated gene 15) by isopeptidases. In this review, current platforms for detecting DUB inhibitors are discussed and the advantages and disadvantages of the approaches are underlined.